The sterol regulatory element‐binding protein 2 is dysregulated by tau alterations in Alzheimer disease. (28th January 2019) - Wang, Chunyu; Zhao, Fanpeng; Shen, Katie; Wang, Wenzhang; Siedlak, Sandra L.; Lee, Hyoung‐gon; Phelix, Clyde F.; Perry, George; Shen, Lu; Tang, Beisha; Yan, Riqiang; Zhu, Xiongwei
Abstract: Disturbed neuronal cholesterol homeostasis has been observed in Alzheimer disease (AD) and contributes to the pathogenesis of AD. As the master switch of cholesterol biosynthesis, the sterol regulatory element‐binding protein 2 (SREBP‐2) translocates to the nucleus after cleavage/activation, but its expression and activation have not been studied in AD which is the focus of the current study. We found both a significant decrease in the nuclear translocation of N‐terminal SREBP‐2 accompanied by a significant accumulation of C‐terminal SREBP‐2 in NFT‐containing pyramidal neurons in AD. N‐terminal‐ SREBP‐2 is also found in dystrophic neurites around plaques in AD brain. Western blot confirmed a significantly reduced nuclear translocation of mature SREBP‐2 (mSREBP‐2) in AD brain. Interestingly, reduced nuclear mSREBP‐2 was only found in animal models of tauopathies such as 3XTg AD mice and P301L Tau Tg mice but not in CRND8 APP transgenic mice, suggesting that tau alterations likely are involved in the changes of mSREBP‐2 distribution and activation in AD. Altogether, our study demonstrated disturbed SREBP‐2 signaling in AD and related models, and proved for the first time that tau alterations contribute to disturbed cholesterol homeostasis in AD likely through modulation of nuclear mSREBP‐2 translocation.